2003
DOI: 10.1002/esp.1035
|View full text |Cite
|
Sign up to set email alerts
|

Wind erosion in a marginal Mediterranean dryland area: a case study from the Khanasser Valley, Syria

Abstract: Evidence of wind erosion is widespread in the drylands of the Mediterranean region. The purpose of this study was to quantify the extent of windblown dust and to assess the factors that affect the susceptibility to wind erosion in areas that are marginal due to their aridity. The study was carried out in Khanasser Valley, a typical degraded, marginal area in northwestern Syria. The average annual rainfall is about 200 mm and falls mainly in the winter months. In the valley floor, cultivation of rainfed barley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The amount of SOM depends on the input of biomass C and its rate of decomposition. The SOM concentration is also extremely low because of the centuries of cultivation by extractive practices, and the losses through accelerated erosion by wind (Masri et al 2003 ) and also water . Pedological factors which reduce the rate of mineralization are the amount of clay and the predominant clay minerals, and nature of exchangeable cations ( Oades 1988 ).…”
Section: Enhancing Resilience Of Soils In the Wana Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of SOM depends on the input of biomass C and its rate of decomposition. The SOM concentration is also extremely low because of the centuries of cultivation by extractive practices, and the losses through accelerated erosion by wind (Masri et al 2003 ) and also water . Pedological factors which reduce the rate of mineralization are the amount of clay and the predominant clay minerals, and nature of exchangeable cations ( Oades 1988 ).…”
Section: Enhancing Resilience Of Soils In the Wana Regionmentioning
confidence: 99%
“…Bessam and Mrabet ( 2003 ) reported that the SOC pool in 0-25 cm layer increased by NT farming at the rate of 1.4 and 0.66 Mg C ha −1 year −1 after 6 and 11 years, respectively. A study conducted in the Khanasser Valley, northwestern Syria, showed that SOM concentration of the airborne sediments exceeded the amount in the parent soil (Masri et al 2003 ). There was some improvement in soil quality of the surface 0-2.5 cm layer (Namr and Mrabet 2004 ).…”
Section: Tillage/residue Managementmentioning
confidence: 99%
“…At an altitude of 350 m above sea level, the valley is rather flat. Annual rainfall ranges from 150 to 250 mm and the rainy season starts in October and ends in May (Masri et al, 2003). Wind in the dry season (from June to September) travels from south to west with exceptional large wind events from other directions.…”
Section: Study Areamentioning
confidence: 99%
“…Wind in the dry season (from June to September) travels from south to west with exceptional large wind events from other directions. During the dry season, the daily average wind speed (at 2 m height) is high and may exceed 10 m s À1 (Masri et al, 2003). Monthly average wind speed in the valley varies from 3.5 m s À1 in the south up to 4.4 m s À1 in the north (Bruggeman et al, 2008).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation